2012
DOI: 10.1093/toxsci/kfs252
|View full text |Cite
|
Sign up to set email alerts
|

Does Methylmercury-Induced Hypercholesterolemia Play a Causal Role in Its Neurotoxicity and Cardiovascular Disease?

Abstract: Methylmercury (MeHg) is an environmental pollutant that biomagnifies throughout the aquatic food chain, thus representing a toxicological concern for humans subsiding on fish for their dietary intake. Although the developing brain is considered the critical target organ of MeHg toxicity, recent evidence indicates that the cardiovascular system may be the most sensitive in adults. However, data on the mechanisms mediating MeHg-induced cardiovascular toxicity are scarce. Based on the close relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…In Bangladesh, drinking from arsenic contaminated wells was associated with increased ALT [578]. Chronic arsenic exposures were also associated with increased triglycerides in a cross-sectional study [579]; in rats, arsenic increased serum cholesterol, triglycerides, free fatty acids and phospholipids in association with increased oxidative stress and hepatic mitochondrial damage [580] as well as ALT when combined with an obesogenic agent [581, 582]. Lead and mercury exposures were associated with the fatty liver surrogate biomarker, ‘unexplained ALT elevation’ in adult NHANES [561]; and lead, but not mercury, was associated with ALT, plasma triglycerides and LDL, in Iranian adolescents [583].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…In Bangladesh, drinking from arsenic contaminated wells was associated with increased ALT [578]. Chronic arsenic exposures were also associated with increased triglycerides in a cross-sectional study [579]; in rats, arsenic increased serum cholesterol, triglycerides, free fatty acids and phospholipids in association with increased oxidative stress and hepatic mitochondrial damage [580] as well as ALT when combined with an obesogenic agent [581, 582]. Lead and mercury exposures were associated with the fatty liver surrogate biomarker, ‘unexplained ALT elevation’ in adult NHANES [561]; and lead, but not mercury, was associated with ALT, plasma triglycerides and LDL, in Iranian adolescents [583].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…Past studies in humans and rodent models indicate that ID and MeHg exposure is associated with dyslipidemia (Nandyala et al, 2013; Stangl and Kirchgessner, 1998; Moreira et al, 2012). Previous studies in Caenorhabditis elegans and Drosophila melanogaster have demonstrated the utility of invertebrate model systems for understanding dysregulation of lipid metabolism in humans (Dourlen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MeHg induced hypercholesterolemia in mice leads to cerebellar glial activation, suggesting MeHg induced dyslipidemia plays a role in both the cardio and neurotoxic effects of MeHg (Moreira et al, 2012). With regard to ID, triglyceride (TAG) serum levels were significantly elevated among Indian adults with ID compared to those who were not; subsequently, Fe therapy among the ID participants significantly decreased TAG levels after 3 months (Nandyala et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…42 In a similar experimental study, the mice treated for 21 days with a drinking solution of methyl mercury (40 mg/L) showed increased total and non-HDL plasma cholesterol levels, supporting the concept of mercury-induced cardiovascular toxicity. 43 Both population and animal studies signify that mercury exposure leads to CVDs, like hypertension, CHD, myocardial infarction, reduction in HRV, increase in sudden cardiac death, increase in carotid IMT and carotid obstruction, generalized atherosclerosis, renal dysfunction, renal failure and proteinuria, and an overall increase in the total cardiovascular mortality. 1,2,4,28,[44][45][46][47][48][49][50][51][52][53] The beginning event that triggers the development of consequent CVD is the functional disruption of the endothelium or endothelial dysfunction, and there is a growing data associating mercury exposure with endothelial dysfunction and higher risk of CVD.…”
Section: Animal Studiesmentioning
confidence: 99%